Early response to cognitive behavioral therapy for body dysmorphic disorder as a predictor of outcomes. (August 2022) - Greenberg, Jennifer L.; Jacobson, Nicholas C.; Hoeppner, Susanne S.; Bernstein, Emily E.; Snorrason, Ivar; Schwartzberg, Anna; Steketee, Gail; Phillips, Katharine A.; Wilhelm, Sabine
Abstract: Individuals with body dysmorphic disorder (BDD) suffer from distressing or impairing preoccupations with perceived imperfections in their appearance. This often-chronic condition is associated with significant functional impairment and elevated rates of psychiatric comorbidity and morbidity, including depression, substance use disorders, and suicidality. Cognitive behavioral therapy (CBT) for BDD has been shown to be efficacious. However, this intervention is long (up to 24 weeks) relative to many manualized approaches for other related conditions, there is a significant shortage of clinicians trained in CBT for BDD, and some patients drop out of treatment and/or do not respond. Thus, there is great interest in understanding and predicting who is most likely to respond, to better allocate clinical resources. This secondary data analysis of participants enrolled in prior uncontrolled and controlled studies of CBT for BDD explored whether early response to CBT, operationalized as percentage change in symptom severity within the first four weeks and the first 12 weeks of this 24-week treatment, predicts clinical outcomes for patients with BDD (n = 90). The findings indicated that minimal early symptom change was not indicative of eventual non-response. This suggests that patients and clinicians should not be discouraged by limited early improvement but should instead continue with a full course of treatment before reevaluating progress and alternative interventions. Overall, the results support the view that treatment success is more likely if a longer CBT protocol is followed. More work is needed to understand mechanisms of change and thus match optimal interventions to patient characteristics. Highlights: Examined early response to CBT for BDD as a potential predictor of outcome. Minimal early symptom change was not indicative of eventual non-response. Patients and clinicians should be encouraged to follow a full course of CBT for BDD.